2009
DOI: 10.1038/nm.2009
|View full text |Cite
|
Sign up to set email alerts
|

An integrin αvβ3–c-Src oncogenic unit promotes anchorage-independence and tumor progression

Abstract: Integrins regulate adhesion-dependent growth, survival and invasion of tumor cells. In particular, expression of integrin αvβ3 is associated with progression of a variety of human tumors. Here, we reveal a novel adhesion-independent role for integrin αvβ3 in pancreatic cancer and other carcinomas. Specifically, αvβ3 expressed in carcinoma cells enhanced anchorage-independent tumor growth in vitro and increased lymph node metastases in vivo. This required recruitment of c-src to the β3 integrin cytoplasmic tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
235
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 260 publications
(256 citation statements)
references
References 44 publications
(55 reference statements)
14
235
0
1
Order By: Relevance
“…In contrast, possible negative roles for FAK in tumour progression have also been reported 12,13 . For example, FAK expression is not a prognostic marker for colon adenocarcinoma patients and FAK expression does not correlate with survival 56 ; loss of tumour FAK is actually associated with increased metastasis in cervical cancer 12 ; pharmacological inhibition of Src can suppress metastasis without affecting FAK activation 57 ; and under some oncogenic conditions, such as those initiated by Ras, metastasis is promoted by dephosphorylating FAK 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, possible negative roles for FAK in tumour progression have also been reported 12,13 . For example, FAK expression is not a prognostic marker for colon adenocarcinoma patients and FAK expression does not correlate with survival 56 ; loss of tumour FAK is actually associated with increased metastasis in cervical cancer 12 ; pharmacological inhibition of Src can suppress metastasis without affecting FAK activation 57 ; and under some oncogenic conditions, such as those initiated by Ras, metastasis is promoted by dephosphorylating FAK 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Integrin α v β 3 is expressed on the most aggressive tumor cells in many cancers including high-grade glioma [21], and its expression correlates with metastasis by recruiting c-Src to integrin β 3 [22]. Recent study has revealed that integrin β 3 is necessary and sufficient to account for stemness and drug resistance by activating Ras/RalB/TBK1/NF-κB pathway [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Both the anchorage-independent growth assays and the orthotopic pancreatic carcinoma model were performed as described (31). Intravital imaging was performed using an Olympus Ovi100 imaging station.…”
Section: Methodsmentioning
confidence: 99%